Sistem Informasi Koran Online Mediator Jambi - -, Afrizal - (Lembaga Penelitian Dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2017)
Online newspaper is an alternative solution as broadcast media and news information to the public. Through a range of online newspapers and news information dissemination more widely. it is an advantage of being able to reach a wider audience that can not be reached by the old reporting system. At this online newspaper browse news content can be updated at any time and every time, we can also be used as a medium for promotion or advertising more efficient. One thing that will not be acquired by the user readers with the old reporting system such as newspaper paper was commenting on the content of the news delivered. With the online newspaper readers are expected to each user involved with the news delivered. Mediator Jambi as a newspaper printing company that requires online newspapers as a medium that will be accessed by the public. From the research conducted, it could be concluded that an online newspaper can be used as a news broadcast media so it can be updated online news content in them and can be commented on by visitors as well as make it easy for people to pair ads.